Pengetahuan Ibu hamil tentang kebutuhan makanan sehat selama kehamilan di BPM T.H Pematangsiantar Tahun 2020 - Zuraidah (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
The proportion of malnutrition anemia among pregnant women in several private practices in Medan is 53.3%. The results of Dolok Saribu’s research in the village of maligas Tonga, Simalungun Regency in 2016 found that pregnant women had anemia with proportion of 57.4% Good nutrition for pregnant women is needed so that fetal growth runs rapidly and does not experience obstacles. The research objective was to describe the knowledge of pregnant women about healthy food consumption patterns in accordance with the growth and development of their pregnancy at BPM T.H. Pematangsiantar in 2020. This research is descriptive with a survey method and uses primary data that has been obtained directly from respondents, the population is 40 pregnant women’s. This data processing by editing, coding, tabulation, entry, cleaning data entry. Based on the results of the study it can be concluded that pregnant women who check their pregnancies at BPM T.H. Pematangsiantar most aged 20-35 years 34 respondents (85%), high school education 22 respondents (55%), housewives work 30 respondents (37.5%). Based on the knowledge of pregnant women about the notion of healthy food during pregnancy, 31 respondents (77.5%) were not good, knowledge of the need for healthy food consumption patterns during pregnancy was not god 20 respondents (50%), knowledge of the positive impact if the need for food consumption patterns 22 respondents (55%) were not well fulfilled and 27 respondents (67.5%) had bad knowledge of hazardous substances. Based on this study, it was found that knowledge of the respondents was not good enough, therefore it is recommended that respondents increase their knowledge about the importance of eating healthy food during pregnancy.